2005
DOI: 10.1002/cne.20816
|View full text |Cite
|
Sign up to set email alerts
|

Differences in spinal distribution and neurochemical phenotype of colonic afferents in mouse and rat

Abstract: Visceral pain is a prevalent clinical problem and one of the most common ailments for which patients seek medical attention. Recent studies have described many of the physiological properties of visceral afferents, but not much is known regarding their anatomical characteristics. To determine the spinal distribution and neurochemical phenotype of colonic afferents in rodents, Alexa Fluor-conjugated cholera toxin-beta (CTB) was injected subserosally into the proximal and distal portions of the descending colon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
121
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(148 citation statements)
references
References 46 publications
(70 reference statements)
18
121
3
Order By: Relevance
“…Similar to previous studies, we found the fluorescent conjugates of CTB to be very efficient in labeling visceral afferents of the pelvis in the rat and mouse (Christianson et al 2006a;Christianson et al 2006b;Wang et al 1998). As expected and in agreement with existing literature (Jancso and Maggi 1987;Robinson et al 2004;Wang et al 1998;Zhong et al 2003), most bladder afferents projected from the L6-S1 DRG in both rodents, while a smaller, but still notable, population was present in TL DRG.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Similar to previous studies, we found the fluorescent conjugates of CTB to be very efficient in labeling visceral afferents of the pelvis in the rat and mouse (Christianson et al 2006a;Christianson et al 2006b;Wang et al 1998). As expected and in agreement with existing literature (Jancso and Maggi 1987;Robinson et al 2004;Wang et al 1998;Zhong et al 2003), most bladder afferents projected from the L6-S1 DRG in both rodents, while a smaller, but still notable, population was present in TL DRG.…”
Section: Discussionsupporting
confidence: 91%
“…As expected and in agreement with existing literature (Jancso and Maggi 1987;Robinson et al 2004;Wang et al 1998;Zhong et al 2003), most bladder afferents projected from the L6-S1 DRG in both rodents, while a smaller, but still notable, population was present in TL DRG. In our studies, the distribution of retrogradelylabeled distal colon afferents also paralleled that of the bladder and, in general, was in agreement with the bimodal LS and TL peaks as noted in the Wistar rat (Vizzard et al 2000) and C57Bl/6 mice (Christianson et al 2006b;Robinson et al 2004). In support of the specificity of our labeling studies, dually-labeled cells were identified only at DRG levels that have previously been shown to contain both distal colon and urinary bladder afferents (Christianson et al 2006b;de Groat et al 1987;Keast and De Groat 1992;Robinson et al 2004).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…bradykinin, 5-HT, neuronal growth factor, tryptase), but also mild acidosis are able to sensitize TRPV1 and enhance the probability of channel gating by heat and capsaicin (Chuang et al, 2001;Ji et al, 2002;Amadesi et al, 2004;Sugiuar et al, 2004). Because TRPV1 was suggested to play a crucial role in nociception based on its expression on mostly unmyelinated visceral afferents (Ward et al, 2003;Brierley et al, 2005;Christianson et al, 2006), a vast number of studies investigating its role in visceral sensation and pain emerged (Caterina et al, 2000). (Reviews by Di Marzo et al, 2002;Geppetti and Trevisani, 2004;Holzer, 2008b;Blackshaw et al, 2010).…”
Section: Trpv Channelsmentioning
confidence: 99%